Apology and Prophecy: The Oriental Christians face to the Crisis of Marcus Aurelius Government - Spléndido, Mariano (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
The objective of this work is to delve into the analysis that the Christians made from their relationship with the roman State during the period of Marcus Aurelius and how the events that marked the imperial life had repercussions on the communities and in their speeches. Each sector within Christianity will propose strategies to face the crisis. From all branches of Christianity will be the protoorthodox one the most preoccupied for the fitting of their speech to the State canons. Their assessment of imperial reality under Marcus Aurelius recognized that the State power was a good refuge to protect from their enemies: heterodox Christians, pagans or adherents to other oriental cults. Equally, the State power didn’t see any threat in Christianity, just simply a scapegoat for the tensions that generated the economical a social crisis. The State operated as the executor of popular rage, giving the legal framework to their discontent.